(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article provides a comprehensive analysis of the phenomenon of isogloss within the framework of areal linguistics. An isogloss represents a geographical boundary marking the area where a specific linguistic feature occurs, thus reflecting the territorial differentiation of language units and the linguistic diversity among dialects. The study explores various types of isoglosses—phonetic, lexical, morphological, and semantic—and examines their intersection zones, which often indicate contact between linguistic communities. Using examples from Uzbek dialects, the research identifies regional variations in vocabulary and traces their geographical limits. The role of isoglosses in reconstructing the historical development of languages, understanding dialectal interrelations, and mapping linguistic influence is also emphasized. Therefore, the phenomenon of isogloss is viewed not only as a dialectological category but also as an essential methodological tool in historical and comparative linguistics.